2017
DOI: 10.1111/cdoe.12285
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in tooth loss: A multinational comparison

Abstract: There is a considerable variation in the magnitude of inequalities in tooth loss across the countries included in this analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 23 publications
6
68
0
4
Order By: Relevance
“…There were nongradient oral health inequalities among the South Korean population according to the NMSC. The finding also confirmed previous theories and studies which reported that oral health inequalities are related to social class or social status . SEP appeared to be closely related to periodontal status and tooth loss, especially for the Korean population as reported by Han et al.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…There were nongradient oral health inequalities among the South Korean population according to the NMSC. The finding also confirmed previous theories and studies which reported that oral health inequalities are related to social class or social status . SEP appeared to be closely related to periodontal status and tooth loss, especially for the Korean population as reported by Han et al.…”
Section: Discussionsupporting
confidence: 91%
“…It was similar with the results of Elani et al. in which the highest education level group had the lowest prevalence of edentulism and had the highest mean number of teeth present . Both results implied that educational level has an important role in oral health.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To clarify the meaning of tooth loss in the epidemiologic context, it would be helpful to use longitudinal data. A few studies report on tooth survival over time or trends in repeated cross-sectional samples [14][15][16][17][18][19] but most rely on self-reported tooth loss with limitations in validity, 14,16,17 or are performed in selected patient groups with limitations in generalizability into the general population. 19,20 To date, the largest published longitudinal analysis of changes in dental status comes from the Dunedin study, a prospective cohort study of approximately 1000 participants born in 1972/1973.…”
Section: Introductionmentioning
confidence: 99%